2023
DOI: 10.3389/fphar.2022.1108776
|View full text |Cite
|
Sign up to set email alerts
|

The role of metabolic reprogramming in pancreatic cancer chemoresistance

Abstract: Pancreatic cancer is characterized by hidden onset, high malignancy, and early metastasis. Although a few cases meet the surgical indications, chemotherapy remains the primary treatment, and the resulting chemoresistance has become an urgent clinical problem that needs to be solved. In recent years, the importance of metabolic reprogramming as one of the hallmarks of cancers in tumorigenesis has been validated. Metabolic reprogramming involves glucose, lipid, and amino acid metabolism and interacts with oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 192 publications
0
7
0
Order By: Relevance
“…On the other hand, the extrinsic aspect of chemotherapy resistance typically revolves around the tumor stroma. The stroma of pancreatic cancer comprises various components such as extracellular matrix (ECM), cancer-associated fibroblasts (CAFs), pancreatic stellate cells (PSCs), inflammatory cells, immune cells (including tumor-associated macrophages), endothelial cells, nerve cells, and other cell types [ 21 , 22 ], all of which play a pivotal role in the development of chemotherapy resistance in pancreatic cancer [ [23] , [24] , [25] , [26] ]. The dense stroma exerts pressure on blood vessels, creating a hypoxic environment that hampers the effective delivery of chemotherapy agents, thereby facilitating tumor progression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the extrinsic aspect of chemotherapy resistance typically revolves around the tumor stroma. The stroma of pancreatic cancer comprises various components such as extracellular matrix (ECM), cancer-associated fibroblasts (CAFs), pancreatic stellate cells (PSCs), inflammatory cells, immune cells (including tumor-associated macrophages), endothelial cells, nerve cells, and other cell types [ 21 , 22 ], all of which play a pivotal role in the development of chemotherapy resistance in pancreatic cancer [ [23] , [24] , [25] , [26] ]. The dense stroma exerts pressure on blood vessels, creating a hypoxic environment that hampers the effective delivery of chemotherapy agents, thereby facilitating tumor progression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming also contributes to the regulation of macrophage activation (reviewed in Lui et al [148]). Overexpression of indoleamine 2,3-dioxygenase 1 (IDO1) in the TME, a tryptophan catabolic enzyme, causes immunosuppression that can be reversed by a small molecule inhibitor, indoximod (IND).…”
Section: Modulation Of the Tumor Immunosuppressive Microenvironmentmentioning
confidence: 99%
“…ACSS2, one of the acyl-CoA synthetase short-chain family members, is a nucleocytosolic enzyme that catalyzes the conversion of acetate to acetyl-CoA, which is highly expressed in various tumors (Liu et al 2022a , b ). It has been proven through in vitro and in vivo experiments that ACSS2 plays an important role in tumor cell survival under hypoxia in lung cancer, breast cancer, melanoma, and colon cancer (Yoshii et al 2009 ).…”
Section: Altered Lipid Metabolism In Cancer Cells Of the Tmementioning
confidence: 99%
“…This collaborative interplay provides favorable conditions for tumor development, growth, and progression (Gonzalez et al 2018 ; Petrova et al 2018 ; Cao 2019 ; Cheng et al 2019 ; Greten and Grivennikov 2019 ; Bui et al 2021 ). Indeed, numerous studies have demonstrated that the communication between cancer cells and surrounding cells in the TME promotes cancer metastasis and confers chemoresistance through the establishment of metabolic reprogramming, which involves the alteration of tumor metabolism (DeBerardinis and Chandel 2016 ; Chen et al 2022 ; Li et al 2022 ; Liu et al 2022a , b ). Metabolic reprogramming and alteration of oncogenic signaling pathways related to metabolic processes have emerged as hallmarks of cancer (Zhu et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%